Desaturation of alkylbenzenes by cytochrome P450(BM3) (CYP102A1). - Whitehouse, C; Bell, S; Wong, L (2008)
A study was conducted to investigate the desaturation of alkylbenezenes by cytochrome P450BM3 (CYP102A1). It was observed during the study that oxidation of alkylbenzenes with CYP102A1 involves a gamut of P450 activity types that are terminal, sub-terminal benzylic and aromatic hydroxylation; terminal and sub-terminal desaturation; and epoxidation of the olefins. It was also found that the desaturation of cumene by CYP102A1 is sensitive to α-deuteration and insensitive to β-deuteration. Intramolecular deuterium isotope study revealed that the first abstraction in the desaturation of valproic acid and ezlopitant by microsomal P450s take place from activated carbon atoms. The increased β-hydroxylation percentages show that the β-carbon lies closer to the ferryl oxygen in the KT5.